2009
DOI: 10.1111/j.1365-2133.2009.09592.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytokeratins 16 and 10 bind to retinoic acid covalently in skin tissue of mice

Abstract: These results raise the possibility that RA binding to cytokeratins in vivo may be involved in the effect of RA on keratinocytes in mouse skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…27 Animal studies have also shown tretinoin to have an effect on cytokeratin 16, which is an important modulator of the wound healing process. 28 However, to date, a direct cause-and-effect relationship has not been established.…”
Section: Histologic Retinoid Effectsmentioning
confidence: 98%
“…27 Animal studies have also shown tretinoin to have an effect on cytokeratin 16, which is an important modulator of the wound healing process. 28 However, to date, a direct cause-and-effect relationship has not been established.…”
Section: Histologic Retinoid Effectsmentioning
confidence: 98%
“…In this study, retinoic acid was reported to bind to a number of proteins, including K10 and K16. 59 However, the physiological importance of these direct interactions needs still to be further explored.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…75 One explanation might be that patients with KRT10-mutations are not as sensitive to the negative effect of retinoid-induced downregulation of both type II keratins (K1 and K2) in the suprabasal compartment as patients with KRT1-mutations 75 or that the mechanism involve the recently reported interaction between retinoids and K10. 59 However, it would be tempting to suggest that RARα ligands would be suitable as intervention for epidermolytic keratinopathies due to either dominant negative K2 mutations (i.e., Ichthyosis bullosa of Siemens; IBS) or K1/10 mutations (epidermolytic ichthyosis) where upregulation of K4/13 might compensate for the retinoid-induced reduction in K1/K10. In the case of IBS, pharmacological silencing of the mutated KRT2 gene by retinoids or Retinoic acid metabolism blocking agents (RAMBAs 76 ) should hypothetically be the perfect treatment and IBS-patients actually respond well to low-dosage of synthetic retinoids.…”
Section: Retinoid Therapy For Keratinization Disorders Of the Skinmentioning
confidence: 99%
“…It is possible that RA-modification of cytokeratins in vivo may be involved in the effects of RA on keratinocytes in mouse skin. 41,42) …”
Section: Retinoylation In Vivomentioning
confidence: 99%
“…Identification of retinoylated proteins may provide insights into new protein networks that could serve as new targets for therapeutic development. 41,42,[46][47][48][49][50] …”
Section: Future Viewmentioning
confidence: 99%